Modeling market value of land plots using GIS - Roman Shulgan; Kateryna Nikolaichuk (Geodesy and Cartography)
This work examines the regulatory framework for expert monetary valuation of land plots. Scientific research on the development and improvement of economic-statistical methods for mass monetary valuation of land plots is analyzed. The peculiarities and advantages of using GIS in the valuation procedure are considered. A structure of the valuation database is developed for the effective selection of comparable plots during valuation by comparing sales prices and market analysis. The valuation database is formed based on data on land plot sales. Price formation factors are analyzed in order to construct an economic-statistical model of market value for land plots in Rivne. Scales of indicator values are proposed for formalizing the assessment of price formation factors. Functions of the ArcGIS are used to establish indicator values. The market value of land plots is modeled using multiple regression analysis. Additionally, a surface of land plot values is constructed, which serves to determine the approximate market value. The model has been verified using GIS tools. An accuracy assessment of the developed model has been carried out.